Advancing biomedical analysis: Harnessing laser-induced graphene for next-gen of low-cost sensor technology - Elsa Maria Materón; Liana Melo Lins de Azevedo; Juliana Martins Dias; Ketley Caroline Rocha Pereira; Gustavo Miguel Sousa; Matheus Santos Dias; Camila Marchetti Maroneze; Daiane Dias; Cecilia de Carvalho Castro Silva (Journal of Pharmaceutical and Biomedical Analysis Open)
As biosensors and biomedical devices gain increasing importance in everyday diagnostics and health status monitoring, the need to develop and improve their reliability and versatility becomes more pronounced. In this context, the search for new materials for biosensors and biomedical devices has intensified, leading to the emergence of laser-induced graphene (LIG) as a promising candidate. LIG's environmentally sustainable nature, cost-effectiveness, and significant potential for large-scale graphene production and directed writing electronics circuits make it very interesting. In this review, we provide an overview of the mechanisms and precursor materials involved in LIG production, strategies to enhance graphene properties through the in-situ generation of hybrid materials via direct laser writing, and the crucial role of LIG in the development of cost-effective, point-of-care, and wearable devices for medical diagnosis and real-time health status monitoring.